Multifunctional Characterization of Fucoidan: Structural Insights and Efficient Removal of Toxic Metal Ions - Castro-Riquelme, Christian Leonardo; López Maldonado, Eduardo Alberto (Journal of Research Updates in Polymer Science, 2025)
In this study, commercial fucoidan was subjected to comprehensive physicochemical and structural characterization to evaluate its potential for removing heavy metal ions from aqueous media. Fourier transform infrared spectroscopy (FTIR) and proton nuclear magnetic resonance (1H NMR) confirmed the presence of sulfated heterofucans, with distinct signals corresponding to carboxyl, sulfate, and sugar ring functionalities. Thermogravimetric analysis (TGA) revealed notable thermal stability, with major degradation occurring above 240 °C. Interaction mechanisms have been proposed on the basis of functional groups, particularly sulfates and carboxylates. Finally, the efficacy of fucoidan for Ni(II), Pb(II), and Cu(II) removal was validated via inductively coupled plasma (ICP) spectroscopy, which revealed removal rates of up to 99.89% for Cu and 99.84% for Pb. These findings highlight the dual role of fucoidan as both a bioactive polymer and a promising biopolymer for wastewater remediation.